Development and preparation of active starch films carrying tea polyphenol. (15th September 2018) - Feng, Mingyue; Yu, Long; Zhu, Peitao; Zhou, Xiangping; Liu, Hongsheng; Yang, Yunyi; Zhou, Jiaqiao; Gao, Chengcheng; Bao, Xianyang; Chen, Pei
Highlights: Starch film incorporated with TP was developed to produce active food packaging. TP was well dispersed in the starch matrix. TP addition improved antioxidant and antimicrobial activity. A new automatic counting method was developed to identify and count the colonies. Abstract: Starch films incorporated with tea polyphenol (TP) were developed to produce active food packaging. The effect of the incorporation of TP with different content on the structure, physicochemical properties, antioxidant activity and antimicrobial activity of the starch films was systematically evaluated. Results showed that TP was well dispersed in the starch matrix, which induced a slight influence on the surface and barrier properties of the films. TP addition led to an important improvement in antioxidant capability, as well as inhibition efficiency against the microorganisms of S. aureus and E. coli . However, a decrease in mechanical properties of films was observed. Moreover, a new automatic counting method which combined the computer vision and machine learning algorithm was developed to identify and count the colonies, and the method performed much faster without subjective uncertainty.